Linking the UN Sustainable Development Goals and African Agenda 2063: Understanding overlaps and gaps between the global goals and continental priorities for Africa. (2022) - Garfias Royo, Margarita; Diep, Loan; Mulligan, Joe; Mukanga, Pascal; Parikh, Priti
Abstract: The UN 2030 Agenda is a global agenda which brings nations together to address global challenges for sustainable development. It is increasingly expected for bilateral and multilateral development projects and programmes in sub-Saharan Africa to address the Sustainable Development Goals (SDGs). However, Africa's agency in steering sustainable development priorities, notably by proposing its own development agenda and achievements' visions such as those contained in the African Agenda 2063 (AA2063), must be better recognised. This paper aims to establish converging links between the SDGs and AA2063. The authors used a structured process to identify and 'map' commonalities between all SDG and AA2063 targets. This process involved reviewing 32, 617 possible connections between the 169 SDG Targets and 193 Agenda 2063 Targets. Key results identified 4, 434 (14%) connections and three approaches for selecting overlapping areas of action: based on strength of connections, number of connections, and a combination of both. By comparing and establishing areas of overlap between the two agendas a discussion around converging and diverging priorities is held, which can in turn inform project design and monitoring and allow development initiatives to consider how they connect with both agendas. The findings could facilitate funders, policy makers and practitioners to leverage multiple benefits through a targeted approach to address both agendas effectively.